Advocating for children's surgery within country health plans: lessons from Nigeria and the global stage - Justina O. Seyi-Olajide; Omolara Faboya; Omolara Williams; Omolara Williams; Kokila Lakhoo; Emmanuel A. Ameh (Frontiers Media S.A., 2023)
BackgroundDespite the growing emphasis on provision of quality safe and affordable surgical care in low- and middle-income countries, and the World Health Assembly resolution 68. 15 on strengthening emergency and essential surgical care and anesthesia as components of universal health coverage, a review of published surgical plans of various countries, revealed a lack of emphasis on children's surgery. Due to the peculiarities of the human resource, infrastructure and equipment required for children's surgery, a lack of deliberate actions and policies targeted at strengthening surgical care for children implies that achieving universal health coverage for children may not be a reality in this setting.MethodsA baseline assessment of children's surgical capacity was conducted in Nigeria as a part of the National Surgical Obstetrics Anesthesia and Nursing Plan (NSOANP) process. The assessment was done using the World Health Organization (WHO) hospital assessment tool modified for children's surgery (Children Surgical Assessment Tool).ResultsSignificant infrastructural gaps were found, with an abysmally low density of pediatric surgeons and anaesthesiologists, poor emergency preparedness, lack of reliable surgical data and non-inclusion of children's surgery in the national strategic health plan. Using the Global Initiative for Children's Surgery's (GICS) Optimal Resources for Children's Surgical Care (OReCS) document and focusing on the strategic goals and priorities, children's surgery was incorporated into the NSOANP. Implementation of the plan is currently ongoing.ConclusionFrom Nigeria's experience, appropriate advocacy and inclusion of children surgery providers in policy making will promote prioritization of children's surgery in country health and surgical plans.